Pengaruh Prinsip Good Corporate Governance Dalam Pengelolaan Refocusing Dana Desa Di Masa Pandemi Dengan Harmonisasi Sebagai Variabel Moderating - Dessy Aryani; Edy Sujana; I Putu Gede Diatmika (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2023)
Abstract This study was conducted to empirically examine the effect of accountability, transparency and participation on the management refocusing of village fundThe population in this study was 129 village officials throughout Buleleng Regency with a total sample of 98 people calculated using the slovin. Data analysis used SEM-PLS Version 3 with a total of 98 respondents who filled out the questionnaire. The results showed that accountability had a positive and insignificant effect on the management refocusing , transparency had a positive and significant effect on the management refocusing , participation had a positive and significant effect on the management  refocusing , harmonization significantly moderated the effect of accountability on the management refocusing of village fundharmonization strengthens the effect of accountability on the management refocusing , harmonization significantly moderates the effect of transparency on the management refocusing , harmonization weakens the effect of transparency on the management refocusing , harmonization significantly moderates the effect of participation on the management refocusing , harmonization weakens the influence of participation on management refocusing village funds. Keywords : Good Corporate Governance, Refocusing Village Funds, Harmonization